PENINGKATAN KINERJA PEGAWAI MELALUI KEPUASAN KERJA : MOTIVASI, GAYA KEPEMIMPINAN DAN IKLIM ORGANISASI (PADA PABRIK TEH DANAU KEMBAR PTP NUSANTARA VI) - Afuan, M.; Tiur Kamelia, Innaka (Journal of Science Education and Management Business, 2022)
This study aims to analyze and prove the effect of Motivation, Leadership Style and Organizational Climate on Employee Performance with Job Satisfaction as Intervening Variables. The population of this research is the employees of The Twin Lakes Factory PTP Nusantara VI. Sampling in this study using the Census Method with a sample of 70 respondents. Collecting data through a questionnaire that has been tested for validity and reliability. The data analysis technique in this study used the SmartPLS 3 Structural Equation Modeling (SEM) method. The results showed that motivation had a positive and insignificant effect on job satisfaction. Leadership Style positive and significant influence on Job Satisfaction. Organizational Climate positive and significant influence on Job Satisfaction. Motivation